Studies Related to Attitude of Teachers towards Teaching Profession: An investigation into the attitude of College teachers towards Teaching Profession in Cooch Behar District of West Bengal (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The holiest place on the earth is not a Temple or a Church or a Mosque but a School. The sacred person in the world is not a Priest or a Pope or a Moullabi but a Teacher. Teacher was compared to a God and treated as a combination of the Trimurty (Brahma, Vishnu and Maheswar) as well as the supreme one i.e., “Guru Brahma, Guru Bishnu, Gurudeb Maheswar, Guru Sakhat Paramabrahma Tasmeisri Gurabe Namah”. According to the Indian culture a child receives his first physical birth from the parents and the second birth of the hands of the teacher. The teacher is given a higher position than parents, because he opines the pupil’s eyes of knowledge and moulds his character. Teacher plays an important role as friend, philosopher guide and helper of the student. The society places high hopes on a teacher. Keeping the importance of Teaching Profession an attempt has made through this study by the investigators to know the attitude of College teachers towards Teaching Profession in Cooch Behar District of West Bengal. The present study was based on survey method, particularly, the normative survey research method. One hundred eighty teachers (both male and female) teaching in Social and General Science streams were taken as representative sample of the whole population. An attitude scale was used for collecting the data. The means of both groups were tested for significance of difference by using ‘CR’ test. It was found that, the attitude of College teachers of Cooch Behar district of West Bengal is neither more favourable nor unfavourable towards Teaching Profession i.e., satisfactory or average in attitude towards Teaching Profession.